Comprehensive Analysis of the Triterpenoid Saponins Biosynthetic Pathway in Anemone flaccida by Transcriptome and Proteome Profiling - Zhan, Chuansong; Li, Xiaohua; Zhao, Zeying; Yang, Tewu; Wang, Xuekui; Luo, Biaobiao; Zhang, Qiyun; Hu, Yanru; Hu, Xuebo (Frontiers in Plant Science, 2016)
In this study, we conducted the tandem transcriptome and proteome profiling of a non-model medicinal plant, A. flaccida. Using Illumina HiSeq 2000 sequencing platform and iTRAQ technique, a total of 46,962 high-quality unigenes were obtained with an average sequence length of 1,310 bp, along with 1473 unique proteins from proteomic analysis. Among the A. flaccida transcripts, 36,617 (77.97 %) showed significant similarity (E-value<1e-5) to the known proteins in the public database. Of the total 46,962 unigenes, 36,617 ORFs (open reading frame) were predicated. By the RPKM (reads per kilobases per million reads) statistics, 14,004 isoforms (unigenes) were found to be upregulated, and 14,090 isoforms (unigenes) were downregulated in the rhizome as compared to those in the leaf. Based on the bioinformatics analysis, all possible enzymes involved in the triterpenoid saponins biosynthetic pathway of A. flaccida were identified, including cytosolic mevalonate pathway (MVA) and the plastidial methylerythritol pathway (MEP). Additionally, a total of 126 putative cytochrome P450 (CYP450) and 32 putative UDP glycosyltransferases were selected as the candidates of triterpenoid saponins modifiers. Among them, 4 of them were annotated as the gene of CYP716A subfamily, the key enzyme in the oleanane-type triterpenoid saponins biosynthetic pathway. Furthermore, based on RNA-Seq and proteome sequencing, as well as quantitative RT-PCR verification, the expression level of gene and protein commit to triterpenoids biosynthesis in the leaf versus the rhizome was compared.